2021
DOI: 10.3889/oamjms.2021.6277
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Coronavirus Disease-19 Pandemic on Sexual Behavior of Marriage People in Indonesia

Abstract: BACKGROUND: The coronavirus disease (COVID-19) pandemic has been a global challenge since its first encounter. It has changed the daily lives of families including the sexual behavior of couples due to public health concerns and government policy to restrict people’s movement. It has changed both interpersonal and partner relationships; the time availability at home, the continued presence of children at home, the fear of infection, and the inability to physically interact with others have changed most people’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Immature sperm have a different morphology from mature spermatozoa, which can explain why the number of immature sperm increased after 6-7 months. 21,22,41,42,43 The duration between baseline and follow-up analysis of 6-7 months could shed a light on the lingering effects of COVID-19 infection on male infertility. Longer observation time would provide the time needed to recover from the COVID-19 impact on male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Immature sperm have a different morphology from mature spermatozoa, which can explain why the number of immature sperm increased after 6-7 months. 21,22,41,42,43 The duration between baseline and follow-up analysis of 6-7 months could shed a light on the lingering effects of COVID-19 infection on male infertility. Longer observation time would provide the time needed to recover from the COVID-19 impact on male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…At second, in contrast to the period before the epidemic, the whole level of college students' interpersonal relationships was slightly higher after the epidemic. The related researches showed that, the epidemic has changed people's interpersonal relationships (Tribowo et al, 2021), and multiply affected the interpersonal relationships in school (Herrmann et al, 2021). However, the difference between college students' interpersonal relationships became larger after the epidemic.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…College students' interpersonal relationship is a kind of external expression of their behavior, revealing their behavioral patter. The epidemic has changed people's interpersonal relationships (Tribowo et al, 2021) and has multiple effects on interpersonal relationships in school (Herrmann et al, 2021). investigated the relationships among Chinese college students' interpersonal relationships, school adjustment, mental resilience and social support in the period of pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic affects couples in Indonesia, whether they have less frequency of sexual activity and decreased desire to have children. This is due to the fear of the pandemic to their life stability (Tribowo, 2021).…”
Section: Introductionmentioning
confidence: 99%